The Study of Buffer Allocation Problem in Complex Production Line - Xiaoyong Pan; Jiang Wu; Quanwei Zhang; Dong Lai; Xin Fu; Chen Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper studies the problem of allocating buffers in stochastic production flow lines with product travel time. We build a model that decomposes the production line into the S-B-S (Station-Buffer-Station) subsystems, and use queueing theory to aggregate the subsystems. Experiments are designed for both balanced and unbalanced production lines, and with the computational results, some general rules for the buffer allocation problem are proposed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4520